PELAKSANAAN PERJANJIAN KREDIT UNTUK USAHA KECIL DAN MENENGAH PADA BANK PEMBANGUNAN DAERAH (BPD) JAWA TIMUR KANTOR CABANG PACITAN - , TIFANI DIANITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to answer the problems concerning default forms done by client on the implementation of credit agreement for small and middle business on BPD at East Java of Pacitan Branch Office and default settlement on the implementation of credit agreement for small and middle business on BPD at East Java of Pacitan Branch Office. This research character is Juridical Empiric and carried out in Pacitan with purposive sampling method, with research respondent that is Section Chief of Credit for Small and Middle Business and Section Assistant of Credit on BPD Bank at East Java of Pacitan Branch Office. With using interview guidelines in semi structured form. This research result shown that default form conducted by the client in the implementation of credit agreement for small and middle business on BPD at East Java of Pacitan Branch Office is because of the client unable to pay the monthly installment payment to the Bank party. And moreover some clients purposely did not pay the installment even though able to pay the installment payment actually. Default settlement in the credit agreement of small and middle business on BPD at East Java taken on non-litigation way that is agreed deliberation through Rescheduling, Reconditioning, and Restructuring line, because this methods gives efficiency and effectiveness for both parties that is creditor and debtor. If after implemented troubled credit settlement through non-litigation lines, but it is still unsuccessful settled internally thus BPD at East Java of Pacitan Branch Office party ceded the settlement to PUPN (National Credit Management Committee). Keywords: Credit agreement, Default